Long-term implications of local industrial clusters - Thomas Brenner; Andreas Gildner (Max Planck Institute of Economics, 2006)
Local industrial clusters have attracted much attention in recent economic and geographic literature. The focus has been on identifying the conditions for the emergence of such clusters. Here the long-term implications of local industrial clusters are studied. To this end, we examine German regions where those that contain long-existing industrial clusters are compared to all other regions. We statistically examine what characterises regions that have contained local industrial clusters for quite some time. The analysis is conducted separately for three industries.
Keywords: 330; local industrial clusters; agglomeration economies; economic development